2021
DOI: 10.23887/ijll.v5i3.45767
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Perception on the Advantages of Group Discussion Technique in Teaching Speaking at the Eleventh Grade in Sman 1 Vii Koto Sungai Sarik

Abstract: This research was due to some problems that were found at 11th grade of SMAN 1 VII Koto. First, some students said that they think the group discussion was good for them to improve their speaking skill. However, there were still some students who do not like group discussion since it makes the classroom become noisy and lost their focus in learning. Then, tends to focus on the students who can ask and answer questions in English correctly. Meanwhile, the students who are shy and cannot speak English fluently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Meanwhile, Yundayani & Kardijan (2018), state that SGD is necessary for students to verbally communicate ideas, engage in discussion, encourage, and group members to speak, SGD indirectly motivate students to develop their speaking skills. Students will naturally understand and solve problems with the experiences they have, which they then think critically Fikrina et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Yundayani & Kardijan (2018), state that SGD is necessary for students to verbally communicate ideas, engage in discussion, encourage, and group members to speak, SGD indirectly motivate students to develop their speaking skills. Students will naturally understand and solve problems with the experiences they have, which they then think critically Fikrina et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, students complete their conceptual understanding from information obtained from discussion partners, so the RCCDE model is very effective in empowering the understanding of marine invertebrate material concepts because it gains a complete understanding both from concept maps, field studies, connections, and discussions, so that answers are found-moreover, solutions to problems or things that were not understood when making the concept map. Previous research has informed that group discussions are good for improving speaking skills, critical thinking, communication skills, and understanding of concepts (Fikrina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%